Characteristics of Dioxin and Furan Emissions from Selected Electric Arc Furnaces in Vietnam - Thuong, Nguyen Van; Huy, Do Quang; Minh, Nguyen Hung (VNU Journal of Science: Earth and Environmental Sciences, 2016)
Abstract: Polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs) released from thermal processes of various industries have urgently concerned. Stack gas samples were collected from selected electric arc furnaces (EAFs) in Vietnam in order to investigation of PCDD/F concentration, congener profile and emission factors. U.S EPA method 23 was used following the requirements for isokinetic sampling of stack gas emission. The quantification of PCDD/Fs was carried out by high resolution gas chromatography, coupled with high resolution mass spectrometry (HRGC/HRMS). The results suggested that mass concentration and TEQ of PCDD/F in stack gas samples from EAFs in Vietnam ranged from 0.077–2.26 ng/Nm 3 and 0.027–0.264 ngTEQ/Nm 3 , respectively. Emission factors of PCDD/Fs are determined in the range of 0.89 – 2.03 µgTEQ/ton of product. Emission factor of PCDD/F from the EAF plants in Vietnam were equivalent to those in some countries in Asia, but higher than those of the industrialized countries in European Union.   Keywords: PCDD/Fs, EAFs, Stack gas, Emission Factors.